Marketing Strategy Analysis in Optimizing Tourism Potential - Nurhayati, Sucinta Tri; Nasution, Muhammad Syukri Albani; Soemitra, Andri (Bandung: Prodi Manajemen FE Universitas Langlangbuana, 2025)
Batu Katak has significant potential to be developed as a leading tourist destination. However, despite its uniqueness and natural attractions, tourist visits to Batu Katak remain relatively low compared to other tourist destinations in Bahorok District, such as Bukit Lawang. This highlights the challenges in maximizing Batu Katak’s tourism potential. This study aims to develop a strategic marketing plan to optimize the tourism potential of Batu Katak Bahorok using SWOT analysis supported by IFAS and EFAS matrices. This study uses a mixed methods approach, combining qualitative and quantitative methodologies Employing a mixed-method approach, data were collected from stakeholders through interviews and questionnaires. The findings place Batu Katak in Quadrant I (growth oriented strategy), indicating strong internal strengths and favorable external opportunities. Key strengths include natural biodiversity and pristine environments, while weaknesses involve poor infrastructure and limited promotion. Opportunities lie in tourism promotion through digital marketing, while threats include environmental risks and competition. The integration of Maqashid Syariah principles in Batu Katak’s tourism development emphasizes a balance between economic, social, and environmental preservation aspects, ensuring that tourism remains sustainable and does not harm living beings or nature.